2001
DOI: 10.1007/s003940170006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-tocopherol, β-carotene and ascorbic acid on oxidative, hormonal and enzymatic exercise stress markers in habitual training activity of professional basketball players

Abstract: The results of the present study suggest that supplementation with alpha-tocopherol, beta-carotene and ascorbic acid might partially account for the hormonal and enzymatic stress marker profile observed during habitual training activity of professional basketball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 35 publications
4
55
0
5
Order By: Relevance
“…Anerobic exercise has been associated with a substantial level of lactic acidosis in both blood and muscle (Packer, 1997) and with a major increase in plasma catecholamine levels (Schroder et al, 2001), resulting in a remarkably increased blood pressure and the almost twofold higher cardiac rate post-training can be attributed to the significant activity of the players' sympathetic system. In this study, TAS was remarkably decreased post-training in players without a-T supplementation, as reported by other authors (Alessio et al, 2000;Cooper et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anerobic exercise has been associated with a substantial level of lactic acidosis in both blood and muscle (Packer, 1997) and with a major increase in plasma catecholamine levels (Schroder et al, 2001), resulting in a remarkably increased blood pressure and the almost twofold higher cardiac rate post-training can be attributed to the significant activity of the players' sympathetic system. In this study, TAS was remarkably decreased post-training in players without a-T supplementation, as reported by other authors (Alessio et al, 2000;Cooper et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…If the increase in the level of oxygen free radicals exceeds the antioxidant defense capacity of the cells, then lipid peroxidation will occur (Schroder et al, 2001). It has been suggested that athletes undergoing strenuous training and competition may experience difficulties to maintain optimal tissue levels of vitamins, even if consuming the recommended daily allowances (Alessio et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study, in which the effect of vitamin E re-enforcement on the exercise which composes oxidative stress has been searched, in the measurements after the exercise, a significant rise was found in CK value (Keong et al, 2006). Schröder et al (2001) expressed a significant increase in the LDH activity in basketballers after 24 h of the exercise.…”
Section: Introductionmentioning
confidence: 90%